Flavors from home : refugees in Kentucky share their stories and comfort foods - Zaring, Aimee (The University Press of Kentucky, 2015)
Each year, the United States legally resettles tens of thousands of refugees who have fled their homelands. Refugees, unlike economic migrants, are forced to leave their countries of origin or are driven out by violence or persecution. As these individuals and their families struggle to adapt to a new culture, the kitchen often becomes one of the few places where they are able to return ""home."" Preparing native cuisine is one way they can find comfort in an unfamiliar land, retain their customs, reconnect with their past, and preserve a sense of identity. In Flavors from Home, Aimee Zaring s.